Societal impacts of marine nitrogen pollution: rapid evidence assessment and future research - Rendon, Olivia Raquel; Arnull, Jessica; Beaumont, Nicola J.; Wilson, A. Meriwether W.; Painter, Stuart C.; Shadiya, Fathmath (Frontiers in Ocean Sustainability, 2024)
Nitrogen pollution is a global problem and to effectively mitigate the effects we need to understand both the ecological and societal impacts. Coral reefs are of particular concern, as they are a critical source of livelihoods, culture, and wellbeing for hundreds of millions of people. Yet they are rapidly declining due to numerous pressures, with nitrogen pollution identified as a top-ranked non-climatic pressure. A Rapid Evidence Assessment was carried out to understand the societal impacts derived from marine nitrogen pollution on coral reefs. The results highlight key research evidence gaps, such as unclear reporting of nitrogen pollution, not distinguishing impacts from nitrogen and other stressors, non-quantification of nitrogen-specific marine and societal impacts, unstudied global regions with high nitrogen pressure, and the need for greater awareness on marine nitrogen pollution. Future research questions are proposed to allow better understanding on how tropical coastal societies are being impacted by marine nitrogen pollution.